Free convection in a porous wavy cavity filled with a nanofluid using Buongiorno's mathematical model with thermal dispersion effect; Applied Mathematics and Computation; Vol. 299 - Sheremet M. A. Mikhail Aleksandrovich (2017, 2017)
Title screen